Evaluasi Perancangan Sistem Informasi Akuntansi Simpan Pinjam Di Koperasi Dian Lestari Jakarta Timur - Wening Estiningsih; Heri Nurranto (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The research objective is to find out the accounting information system at Dian Lestari savings and loan Cooperative, East Jakarta. In further analysis, this study analyzes and designs an accounting information system that can be applied in the cooperative. Data were collected through interviews, observation and secondary data in the form of documents. Data analysis techniques using qualitative data analysis with an inductive approach. The results showed that the savings and loan accounting system at the Dian Lestari Cooperative had several shortcomings and weaknesses, namely manual records, inadequate reporting coordination between devices in the cooperative and the lack of accuracy in reporting or recording. The design of the savings and loan accounting information system proposed by the researcher is designed to be able to overcome existing weaknesses or deficiencies tailored to the needs of the cooperative